SAT0459 The Influence of Immunosuppressive Treatment on Microangiopathy in Systemic Sclerosis as Measured with Nailfold Videocapillaroscopy. (9th June 2015) - Meijs, J.; de Boer, B.; Schouffoer, A.; Huizinga, T.; Putter, H.; de Vries-Bouwstra, J.
Abstract : Background: Microangiopathy in systemic sclerosis (SSc), as visualized by nailfold videocapillaroscopy (NVC), is a dynamic and sequential process (1). In time, NVC patterns progress from early, to active and finally late SSc pattern. A relation between reverse transition of NVC patterns and treatment with immunosuppressive drugs has been suggested in small studies (2;3). Objectives: To evaluate prevalence of transition of NVC patterns in 138 patients with SSc over time, and to evaluate the influence of immunosuppressive treatment on rate and direction of NVC transition. Methods: NVC was performed annually in SSc patients participating in a multidisciplinary health care program. Patients were included if at least two NVCs were performed. NVC was analyzed by qualitative assessment (pattern recognition). The frequency of stable, progressive and reverse transition of the NVC patterns was assessed. In order to asses the association between immunosuppressive treatment and relative rates of transition of NVC patterns a maximum likelihood estimation in a multistate model was used (Figure 1 ). For the current analysis, influence of autologous hemopoetic stem cell transplantation (HSCT) and cyclophosphamide was evaluated, adjusted for age, gender and disease duration.The hypothesis is that treatment can either decrease the rate of progressive NVC patterns or lead to rapid reverse transition. Results: In 98 patients, NVC was performed twice, in 35 patients NVC was performed 3 times and in 5 patients NVC was performed 4 times. Included patients were mostly females (82%), had a mean age of 51 years and median disease duration of 3 years. At baseline, 6 patients had a normal/aspecific pattern, 4 borderline changes, 13 early pattern, 54 active pattern, and 61 late SSc pattern. Over time, NVC pattern was stable in 53%, progressive in 21% and 26% showed reverse transition. Treatment with HSCT was significantly associated with higher rate of reverse transition (relative transition rates [95% CI] 5.382 [1.0047-28.83]), but not with a decreased rate of progression (4.393, [0.7232-26.68]). No association between cyclophosphamide and rate and direction of transition of NVC pattern was found. Conclusions: Transition of NVC pattern was observed in 47% of SSc patients; 26% showed reverse transition. Rapid reverse transition was associated with treatment with HSCT. This observation could indicate that aggressive immunosuppressive treatment like HSCT can ameliorate microangiopathy in SSc, and advocates further research to unravel the link between microangiopathy and autoimmunity in SSc. References: Sulli A, Pizzorni C, Smith V, Zampogna G, Ravera F, Cutolo M. Timing of transition between capillaroscopic patterns in systemic sclerosis. Arthritis Rheum 2012 March;64(3):821-5. Aschwanden M, Daikeler T, Jaeger KA, Thalhammer C, Gratwohl A, Matucci-Cerinic M, et al. Rapid improvement of nailfold capillaroscopy after intense immunosuppression for systemic sclerosis and mixed connective tissue disease. Ann Rheum Dis 2008;67(7):1057-9. Fleming JN, Nash RA, McLeod DO, Fiorentino DF, Shulman HM, Connolly MK, et al. Capillary regeneration in scleroderma: stem cell therapy reverses phenotype? PLoS One 2008;3(1):e1452. Disclosure of Interest: None declared